INDUSTRI SEMEN INDONESIA DALAM PERSPEKTIF HUKUM ISLAM - Basir Basir (Fakultas Syariah dan hukum Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
Based on the opinion of the scholars and the Anti-monopoly Law we have that the pricing and distribution of the cement dispersal area in Indonesia has included the monopoly, although cement is not the basic needs of the community, but cement is the main ingredient in building the infrastructure by the community. And the cleric also stated that the monopoly is not only on the essential ingredients but also the goods that are needed by the society, and the great scholar Ibn Qudamah also explained that the pricing has also been included into the monopoly. If we look from the cement industry today has met the elements presented by these scholars, pricing, cement into the needs of society, and there is only one product in each region.